Synthesis of ag2s quantum dots and their biomedical applications - CORREA ESPINOZA, SUSANA (2018)
In the last years Quantum dots have been studied from various perspectives from basic science such as physics to nanotechnology and biotechnology with its possible applications in different areas such as sensors, biosensors, lasers, NEMs, semiconductors, green energy, environmental and biomedical applications. This review briefly describes the properties, confinement and synthesis of QDs as well as the performance of QDs in different biomedical applications.